Evaluation of efficacy of foldscope - a paper microscope to be used as a chairside diagnostic tool in oral dysplastic lesions: A comparative study - Roshni Rameshbabu; A H Harini Priya; R Sathish Muthukumar; Krithigaa Sivaraman; D Uthra (Wolters Kluwer Medknow Publications, 2021)
Introduction: Precancerous lesion of the oral mucosa consists of a group of diseases which sometimes resemble each other leaving the clinician in a diagnostic dilemma. Etiology of these diseases varies geographically with most frequently being tobacco use, alcohol drinking, chewing of betel quid containing areca nut, and solar rays. The long-standing practice of these lifestyle habits causes an alteration in the mucosal barrier level leading to malignant transformation. Earlier, the diagnosis of malignant transformation was confirmed using biopsy, but the advent of exfoliative cytology showed that histological features of a cell undergoing transformation are distinctive during early stages. Early diagnosis can be lifesaving, along with chairside adjunct tools that can facilitate the clinician for better diagnosis and use it as an explanatory tool for patients. Aim: The aim of this study was to test the efficacy of foldscope as a chairside diagnostic tool to detect dysplastic changes in potentially malignant lesions affecting the oral cavity. Materials and Methods: This was a cross-sectional comparative study of a total of 54 individuals clinically diagnosed with oral premalignant lesions. Exfoliative cytological smears were taken and observed under light microscope and foldscope. After Papanicolaou stain, it was subjected to cytomorphometric analysis. Results: Cytological changes in potentially malignant lesions detected using foldscope were appreciable and found to be a mirror image of the routine light microscope. Conclusion: Morphological parameters assessed by foldscope proved to be employed in routine practice as well as in the mass screening of oral lesions.